Preoperative incisional and intraoperative frozen section biopsy techniques have comparable accuracy in the diagnosis of benign intraosseous jaw pathology. - Guthrie D; Peacock ZS; Sadow P; Dodson TB; August M (Journal of Oral & Maxillofacial Surgery (02782391), 2012)
PURPOSE: To compare the accuracy of intraoperative frozen section (FS) and preoperative incisional biopsy (IB) techniques to diagnose benign intraosseous jaw lesions. MATERIALS AND METHODS: This is a retrospective cohort study composed of subjects with benign intraosseous jaw lesions. The predictor variable was the technique for establishing a preliminary diagnosis of the lesion, preoperative IB or intraoperative FS. The outcome variable was the accuracy of the biopsy technique when compared with the final histologic diagnosis and was classified as concordant or discordant. The comparative diagnostic accuracy of the techniques was assessed with the [chi](2) test. RESULTS: A total of 71 subjects met inclusion criteria. The mean age was 39 years (range, 5 to 85 years), and 58% (41) were male patients. Of the subjects, 20 (28%) underwent IB. In 14 (70%) of these, the results of biopsy agreed with the final diagnosis. 51 (72%) underwent intraoperative FS and in 31 (62%) of these, the results of biopsy agreed with the final diagnosis. The difference in diagnostic accuracy between IB (70%) and FS (61%) was statistically insignificant (P = .48). Sources of biopsy error included sampling error (46%), insufficient epithelial tissue (15%), inflammation (15%), pathologist's experience (8%), and artifact (4%). CONCLUSIONS: Preoperative IB and intraoperative FS provide comparable accuracy of diagnosis in patients with benign intraosseous jaw pathology. Sampling error was the most common reason for discordant results.